Strengths and Limitations of Nitrogen Rate Recommendations for Corn and Opportunities for Improvement. (1st January 2018) - Morris, Thomas F.; Murrell, T. Scott; Beegle, Douglas B.; Camberato, James J.; Ferguson, Richard B.; Grove, John; Ketterings, Quirine; Kyveryga, Peter M.; Laboski, Carrie A.M.; McGrath, Joshua M.; Meisinger, John J.; Melkonian, Jeff; et al.
Abstract : Core Ideas: Nitrogen recommendations for individual corn fields are less accurate than desired. Nitrogen recommendations need improvement for economic and environmental reasons. A review of fundamental concepts will improve understanding about N recommendations. Examination of N recommendation systems, tests, and models will improve recommendations. Nitrogen fixation by the Haber–Bosch process has more than doubled the amount of fixed N on Earth, significantly influencing the global N cycle. Much of this fixed N is made into N fertilizer that is used to produce nearly half of the world's food. Too much of the N fertilizer pollutes air and water when it is lost from agroecosystems through volatilization, denitrification, leaching, and runoff. Most of the N fertilizer used in the United States is applied to corn ( Zea mays L.), and the profitability and environmental footprint of corn production is directly tied to N fertilizer applications. Accurately predicting the amount of N needed by corn, however, has proven to be challenging because of the effects of rainfall, temperature, and interactions with soil properties on the N cycle. For this reason, improving N recommendations is critical for profitable corn production and for reducing N losses to the environment. The objectives of this paper were to review current methods for estimating N needs of corn by: (i) reviewing fundamental background information about how N recommendations are created; (ii) evaluating the performance, strengths, and limitations of systems and tools used for making N fertilizer recommendations; (iii) discussing how adaptive management principles and methods can improve recommendations; and (iv) providing a framework for improving N fertilizer rate recommendations.